Hydrazine dihydrochloride as a new additive to promote the performance of tin-based mixed organic cation perovskite solar cells. Issue 10 (26th April 2021) - You, Jiayu; Wang, Meng; Xu, Cunyun; Yao, Yanqing; Zhao, Xusheng; Liu, Debei; Dong, Jun; Guo, Pengju; Xu, Gaobo; Luo, Chuanyao; Zhong, Yuanxin; Song, Qunliang
Abstract : This work provides an easy approach to achieve a high performance of tin based perovskite solar cells via introducing the reductive additive of N2 H4 ·2HCl into the perovskite precursor. Abstract : Toxicity of lead is one of the main hindrances to the commercial application of lead-based halide perovskite solar cells. The best choice to solve this problem of toxicity is to change the perovskite materials from lead-based to tin-based. However, the development of tin-based perovskite solar cells (TPSCs) was slow during the past few years due to their low power conversion efficiency (PCE) which is caused by the existence of Sn 4+ and too fast crystallization of the perovskite during fabrication. Here, for the first time, we introduced an additive of hydrazine dihydrochloride (N2 H4 ·2HCl) powder into the precursor solution of mixed organic cation all-tin perovskite (FA0.75 MA0.25 SnI3 ). The addition of the hydrazine salt effectively inhibited the oxidation of Sn 2+ into Sn 4+ in the perovskite film and adjusted the crystallization process at the same time. By optimizing the concentration of the additive, we finally obtained a PCE of 9.26% with good reproducibility and stability. After 55 days of storage in a N2 -filled glovebox, the unencapsulated device retained ∼90% of the initial efficiency. What is gratifying is that the introduction of the additive also greatly reduced the hysteresis of the devices compared with devices without any additives. Our work shows that the introduction of a small amount of additive into the all-tin perovskite precursor can greatly improve the performance of TPSCs.